(untitled) (Bangladesh Journal of Botany, 2022)
Relationship between the yield and physiological characters in accelerated aged seeds of two varieties and three advanced breeding lines of barnyard millet were tested. Two different methods of seed ageing process were used and a non-significant relationship between the methods was found. It indicates that either of this can be used for accelerated seed ageing process. All the lines showed clear deterioration during the ageing process and there was a clear difference between the different genotypes of barnyard millet. MDU 1 endured well and ACM- 12-110 deteriorated more during the ageing process. The germination per cent and vigour index showed a significantly high correlation with the single plant yield, whereas dry matter production showed a significant relationship with the green fodder yield. Bangladesh J. Bot. 51(1): 169-173, 2022 (March)